Interface modification compound, interface modification layer, perovskite solar cell and preparation method

By using an interface modification layer containing carbazole groups on the nickel oxide hole transport layer of perovskite solar cells, the problem of uneven coverage of perovskite absorber layer is solved, and the photoelectric conversion efficiency and performance stability are improved. It is suitable for Large-scale production.

CN119320328APending Publication Date: 2025-01-17TRINA SOLAR CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411438442.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

It is difficult for existing perovskite solar cells to achieve uniform coverage of the perovskite light absorbing layer on the nickel oxide hole transport layer, resulting in poor photoelectric conversion efficiency and performance repeatability, and are not suitable for large-area production.

Method used

Interface modification layer composed of self-assembled molecules containing carbazole groups and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] and A modified molecules , a uniform interface modification layer is formed on the nickel oxide surface by liquid or vapor deposition method, thereby enhancing the wetting and coverage of the perovskite light absorbing layer.

Benefits of technology

It significantly improves the photoelectric conversion efficiency and performance stability of perovskite solar cells, is suitable for large-area production, and is suitable for nickel oxide surfaces prepared by vacuum method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320328A_ABST
    Figure CN119320328A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of perovskite solar cells, and particularly relates to an interface modification compound, an interface modification layer, a perovskite solar cell and a preparation method. The interface modification compound is a compound shown as a formula I or a compound shown as a formula II, and the definitions of all groups in the formula I and the formula II are described in the specification. The interface modification layer containing the interface modification compound can effectively improve the wettability and the coverage rate of a perovskite solution on the surface of a hole transport layer, so that the photoelectric conversion efficiency and the performance repeatability of the perovskite solar cell are improved, and large-area production is realized. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of perovskite solar cells, and specifically relates to an interface modification compound, an interface modification layer, a perovskite solar cell and a preparation method. Background Art

[0002] Organic-inorganic perovskite solar cells have made rapid progress in recent years due to their advantages such as low preparation cost, high theoretical efficiency, and adjustable band gap. In the past decade, the photoelectric conversion efficiency of this type of solar cell has increased from 3.8% to 26.1%, which is very close to the highest photoelectric conversion efficiency of traditional silicon-based solar cells. As a perovskite cell, the perovskite / crystalline silicon tandem cell currently has a photoelectric conversion efficiency of 33.9%, which has a higher theoretical limit efficiency.

[0003] The device structure of perovskite solar cells can be divided into a formal structure and a trans structure, wherein the structure of the trans device is composed of a transparent conductive substrate, a hole transport layer, a perovskite light absorbing layer, an electron transport layer and a metal electrode starting from the light incident surface. Among them, the commonly used hole transport layer materials are generally selected from poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA), nickel oxide (NiOx), poly 3,4-ethylenedioxythiophene and polystyrene sulfonate (PEDOT:PSS). Based on cost and large-scale production considerations, nickel oxide materials are generally used as hole transport layer materials. However, due to the poor charge transfer ability between nickel oxide and the perovskite light absorbing layer, the corresponding device performance is very poor. Generally, an interface modification layer such as self-assembled monolayer (SAMs) is deposited between nickel oxide and the perovskite light absorbing layer to enhance the charge transfer performance, thereby improving the photoelectric conversion efficiency of the device.

[0004] There are two methods for the deposition and preparation of nickel oxide materials: solution method and vacuum deposition method. Based on considerations such as mass production and large-scale production, vacuum deposition methods such as magnetron sputtering are generally used to prepare nickel oxide. However, on the one hand, nickel oxide prepared by vacuum deposition methods such as magnetron sputtering has an amorphous structure, and the surface of the prepared substrate grows uniformly, resulting in a surface roughness that is very small compared to nanocrystals, which in turn affects the wettability of the substrate to the perovskite solution; on the other hand, the surface modification materials that generally improve device performance have very poor wettability to the perovskite solution. Therefore, due to the above two reasons, when preparing the perovskite light-absorbing layer, it is impossible to achieve uniform coverage of the perovskite film on the surface of the surface-modified nickel oxide, which seriously affects the photoelectric conversion efficiency, performance repeatability and large-scale production of perovskite and perovskite / crystalline silicon stacked solar cells.

[0005] Therefore, there is an urgent need to develop an interface modification material that can improve the wettability of the perovskite light absorbing layer solution on the nickel oxide hole transport layer substrate and the surface coverage of the perovskite light absorbing layer, thereby improving the photoelectric conversion efficiency and performance repeatability of perovskite solar cells and realizing large-scale production of perovskite solar cells. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides an interface modification compound. The interface modification layer is formed by depositing a self-assembled molecule containing a carbazole group or a type B modification molecule of poly [bis(4-phenyl)(2,4,6-trimethylphenyl)amine] and a type A modification molecule of a structure of formula I or formula II on the surface of a nickel oxide hole transport layer. The structure can effectively improve the wettability of a nickel oxide substrate plus an interface modification layer prepared by a vacuum method to a perovskite solution, and achieve uniform coverage of a perovskite light absorbing layer on the nickel oxide substrate plus an interface modification layer prepared by a vacuum method, thereby obtaining a perovskite solar cell with excellent device performance, stable performance, and large-scale production.

[0007] Specifically, the present invention provides an interface modification compound, wherein the interface modification compound is a compound of formula I or a compound of formula II:

[0008]

[0009] In Formula I, R 1 -R 5 are each independently selected from H, F, C1-C10 alkyl which is unsubstituted or substituted by one or more fluorine groups, and R 1 -R 5 At least one of them is F or a C1-C10 alkyl group substituted by one or more fluorine groups; R 6 is a single bond, unsubstituted or substituted C1-C10 alkylene; X is a hydrophilic group;

[0010]

[0011] In Formula II, R 7 -R 16 are each independently selected from H, F, C1-C10 alkyl which is unsubstituted or substituted by one or more fluorine groups, and R 7 -R 16 At least one of them is F or a C1-C10 alkyl group substituted by one or more fluorine groups; R 17 and R 18 Each is independently a single bond, an unsubstituted or substituted C1-C10 alkylene group; X' is a hydrophilic group.

[0012] In one or more embodiments, in Formula I, R 1 -R 5 Each independently selected from H, F and -CF3 , and R 1 -R 5 At least one of them is F or -CF 3 .

[0013] In one or more embodiments, in Formula I, R 6 It is a C1-C6 alkylene group.

[0014] In one or more embodiments, in Formula I, X is -NH 2 、-NH 3 + Y - 、-NR 2 or -N + R 3 Y - , wherein R is a C1-C10 alkyl group and Y is a halogen group.

[0015] In one or more embodiments, in Formula II, R 7 -R 16 Each independently selected from H, F and -CF 3 , and R 7 -R 16 At least one of them is F or -CF 3 .

[0016] In one or more embodiments, in Formula II, R 7 -R 11 At least one of them is F or -CF 3 And R 12 -R 16 At least one of them is F or -CF 3 .

[0017] In one or more embodiments, in Formula II, R 17 and R 18 Each is independently a C1-C6 alkylene group.

[0018] In one or more embodiments, in Formula II, X' is -NH-, -NH 2 + Y - -, -NR-, or -N + R 2 Y - -, wherein R is a C1-C10 alkyl group and Y is a halogen group.

[0019] In one or more embodiments, the interface modifying compound may be selected from the following compounds:

[0020]

[0021] In one or more embodiments, the interface modification compound is 4-fluorophenethylammonium chloride or 4-fluorophenethylammonium iodide.

[0022] The present invention provides an interface modification layer, which comprises a type A modification molecule and a type B modification molecule, wherein the type A modification molecule is one or more of the interface modification compounds described in the present invention, and the type B modification molecule is selected from one or more of a self-assembly molecule containing a carbazole group and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine].

[0023] In one or more embodiments, the self-assembling molecule containing carbazole groups is [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid and / or [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid.

[0024] In one or more embodiments, in the interface modification layer, the mass ratio of the type B modification molecules to the type A modification molecules is 1:(0.1-50).

[0025] In one or more embodiments, the thickness of the interface modification layer is 2-5 nm.

[0026] The present invention provides a method for preparing the interface modification layer of the present invention, and the method comprises the following steps: depositing the interface modification layer by liquid phase deposition method or vapor phase deposition method.

[0027] In one or more embodiments, the interface modification layer is deposited by a liquid deposition method, which includes dissolving the material of the interface modification layer in a solvent to obtain an interface modification layer solution, and then using the interface modification layer solution to deposit the interface modification layer.

[0028] In one or more embodiments, the deposition of the interface modification layer is performed in air or a protective atmosphere.

[0029] In one or more embodiments, the liquid deposition method is an immersion method or a spin coating method.

[0030] In one or more embodiments, the solvent of the interface modification layer solution is selected from one or more of isopropanol, ethanol and methanol.

[0031] In one or more embodiments, the concentration of the type B modifying molecules in the interface modification layer solution is 0.1-5 mg / mL.

[0032] In one or more embodiments, the concentration of the type A modifying molecule in the interface modification layer solution is 0.1-1.0 mg / mL.

[0033] In one or more embodiments, the method further comprises the steps of performing a first heat treatment, cleaning, and a second heat treatment after the interface modification layer is deposited.

[0034] In one or more embodiments, the temperature of the first heat treatment is 80-150°C.

[0035] In one or more embodiments, the first heat treatment is performed for 5-10 minutes.

[0036] In one or more embodiments, the cleaning agent in the cleaning process is selected from one or more of isopropanol, ethanol and methanol.

[0037] In one or more embodiments, the temperature of the secondary heat treatment is 80-150°C.

[0038] In one or more embodiments, the reheat treatment time is 5-10 minutes.

[0039] The present invention provides a perovskite solar cell, wherein the perovskite solar cell comprises the interface modification layer of the present invention.

[0040] In one or more embodiments, the perovskite solar cell includes, in order from the thickness direction, a transparent conductive substrate, a hole transport layer, an interface modification layer, a perovskite light absorption layer, an electron transport layer and a metal electrode.

[0041] In one or more embodiments, the transparent conductive substrate is a transparent conductive glass substrate, one or more of an indium tin oxide transparent conductive glass substrate, a fluorine-doped tin oxide transparent conductive glass substrate, an indium zinc oxide transparent conductive glass substrate, an aluminum-doped zinc oxide transparent conductive glass substrate, an antimony-doped tin oxide transparent conductive glass substrate, a cerium-doped indium oxide transparent conductive glass substrate, and a tungsten-doped indium oxide transparent conductive glass substrate.

[0042] In one or more embodiments, the hole transport layer comprises nickel oxide.

[0043] In one or more embodiments, the mass fraction of the nickel oxide in the hole transport layer is ≥ 95%.

[0044] In one or more embodiments, the nickel oxide in the hole transport layer has an amorphous structure.

[0045] In one or more embodiments, the hole transport layer further comprises a metal oxide other than nickel oxide. Preferably, the metal in the metal oxide is selected from one or more of Li, Cu, Na, Mg, Ca, Sr, Ba and Au.

[0046] In one or more embodiments, the hole transport layer has a thickness of 15-30 nm.

[0047] In one or more embodiments, the perovskite light absorbing layer is ABY 3 A perovskite light-absorbing material with a structure; wherein the A-site ion is selected from one or more of a cesium ion, a methylamino group and a methylamine group, the B-site ion is a lead ion and / or a tin ion, and the Y-site ion is selected from one or more of an iodide ion, a bromide ion and a chloride ion.

[0048] In one or more embodiments, the thickness of the perovskite light absorbing layer is 400-1000 nm.

[0049] In one or more embodiments, the electron transport layer includes a first electron transport layer and a second electron transport layer in sequence from the thickness direction; preferably, the first electron transport layer is C60, and the second electron transport layer is 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline; preferably, the thickness of the first electron transport layer is 10-40nm, and the thickness of the second electron transport layer is 5-10nm.

[0050] In one or more embodiments, the thickness of the electron transport layer is 15-50 nm. In one or more embodiments, the metal electrode is Cu, Ag or Al.

[0051] In one or more embodiments, the thickness of the metal electrode is 100-1000 nm.

[0052] The present invention provides a method for preparing the perovskite solar cell of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 Schematic diagram of the structure of perovskite solar cells according to some embodiments of the present invention.

[0054] Figure 2 Optical comparison photos of the perovskite light absorption layer (a) of the perovskite solar cell prepared in Comparative Example 1 and the perovskite light absorption layer (b) of the perovskite solar cell prepared in Example 1.

[0055] Figure 3 Optical comparison photos of the glass surface of the perovskite solar cell prepared in Comparative Example 1 (a) and the glass surface of the perovskite solar cell prepared in Example 1 (b). DETAILED DESCRIPTION

[0056] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0057] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0058] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0059] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0060] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.

[0061] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0062] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0063] The present invention provides an interface modification compound, characterized in that the interface modification compound is a compound of formula I or a compound of formula II:

[0064]

[0065] In Formula I, R 1 -R 5 are each independently selected from H, F, C1-C10 alkyl which is unsubstituted or substituted by one or more fluorine groups, and R1 -R 5 At least one of them is F or a C1-C10 alkyl group substituted by one or more fluorine groups; R 6 is a single bond, unsubstituted or substituted C1-C10 alkylene; X is a hydrophilic group;

[0066]

[0067] In Formula II, R 7 -R 16 are each independently selected from H, F, C1-C10 alkyl which is unsubstituted or substituted by one or more fluorine groups, and R 7 -R 16 At least one of them is F or a C1-C10 alkyl group substituted by one or more fluorine groups; R 17 and R 18 Each is independently a single bond, an unsubstituted or substituted C1-C10 alkylene group; X' is a hydrophilic group.

[0068] In the present invention, one end of the interface modification compound is a fluorine-containing group. Due to the electronegativity of fluorine, the interface modification compound can be combined with the nickel oxide surface of the hole transport layer to ensure the orientation of the modified material on the nickel oxide surface and modify the nickel oxide surface; the other end of the interface modification compound is a hydrophilic group. Since the hydrophilic group can be combined with the perovskite light absorption layer material, it helps to improve the wettability of the substrate after deposition to the perovskite light absorption layer solution; at the same time, the introduction of the interface modification compound can make the B-type modification molecule more evenly distributed on the surface of the nickel oxide, reduce the anchoring number and residual number of the first modification molecule on the surface of the nickel oxide, and the interface modification compound does not affect the deposition of the B-type modification molecule. On the basis of, the uniform deposition of the B-type modification molecule is helpful. In summary, the interface modification compound can not only improve the wettability of the perovskite light absorption layer, but also promote the high-quality deposition of self-assembled molecules, thereby improving the device performance and long-term stability of the perovskite solar cell.

[0069] In Formula I of the present invention, R 1 -R 5 can be independently selected from H, F and -CF 3 , and R 1 -R 5 At least one of them is F or -CF 3 .

[0070] In some embodiments, R 1 -R 5 One is F, two are F, and one is CF 3 , two for CF 3 .

[0071] In some embodiments, R 1 -R5 There are two F or CF 3 , in which case the position of the substituent can be the ortho, para or meta position.

[0072] In Formula I of the present invention, R 6 It may be a C1-C6 alkylene group.

[0073] In Formula I of the present invention, X can be -NH 2 、-NH 3 + Y - 、-NR 2 or -N + R 3 Y - , wherein R may be a C1-C10 alkyl group and Y may be a halogen group.

[0074] In Formula II of the present invention, R 7 -R 16 can be independently selected from H, F and -CF 3 , and R 7 -R 16 At least one of them is F or -CF 3 Preferably, R 7 -R 11 At least one of them is F or -CF 3 And R 12 -R 16 At least one of them is F or -CF 3 .

[0075] In some embodiments, R 7 -R 11 One is F, two are F, and one is CF 3 , two for CF 3 ; R 12 -R 16 One is F, two are F, and one is CF 3 , two for CF 3 .

[0076] In some embodiments, R 7 -R 11 There are two F or CF 3 , in which case the position of the substituent can be the ortho, para or meta position.

[0077] In some embodiments, R 12 -R 16 There are two F or CF 3 , in which case the position of the substituent can be the ortho, para or meta position.

[0078] In Formula II of the present invention, R17 and R 18 They may each independently be a C1-C6 alkylene group.

[0079] In Formula II of the present invention, X' can be -NH-, -NH 2 + Y - -, -NR-, or -N + R 2 Y - -, wherein R may be a C1-C10 alkyl group and Y may be a halogen group.

[0080] In the present invention, the interface modification compound may be selected from the following compounds:

[0081]

[0082] In the present invention, the use of the above-mentioned interface modification compound is beneficial to improving the wettability of the perovskite light-absorbing layer, promoting high-quality deposition of self-assembled molecules, and thus improving the device performance and long-term stability of the perovskite solar cell.

[0083] In some embodiments, the interface modification compound may be 4-fluorophenethylammonium chloride (4-F-PEACl) or 4-fluorophenethylammonium iodide (4-F-PEAI).

[0084] In the present invention, the interface modification layer may include a class B modification molecule and a class A modification molecule, the class A modification molecule may be one or more of the interface modification compounds of the present invention, and the class B modification molecule may be one or more of a self-assembling molecule containing a carbazole group and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine](PTAA). In some embodiments, the self-assembling molecule containing a carbazole group may be [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) and / or [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz). In the present invention, the use of the above-mentioned class B modification molecules can modify the surface of nickel oxide, thereby improving the device performance of the perovskite solar cell.

[0085] In the present invention, in the interface modification layer, the mass ratio of the class B modification molecule to the class A modification molecule can be 1:(0.1-50), preferably 1:(0.1-10); for example, 1:0.1, 1:0.2, 1:0.5, 1:0.8, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10. In the present invention, controlling the mass ratio of the class B modification molecule to the class A modification molecule within the above preferred range is beneficial to improving the hole transport ability of the solar cell and the wettability to the perovskite solution, thereby helping to improve the device performance of the perovskite solar cell.

[0086] In the present invention, the thickness of the interface modification layer can be 2-5 nm, for example, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm.

[0087] In the present invention, the interface modification layer can be deposited by liquid phase deposition or vapor phase deposition; preferably, the interface modification layer can be deposited by liquid phase deposition. In some embodiments, the liquid phase deposition method can be an immersion method or a spin coating method, preferably a spin coating method.

[0088] In the present invention, when the spin coating method is used for deposition, the sample may be soaked before the spin coating, and the soaking time may be 10-300s, such as 10s, 20s, 50s, 80s, 100s, 120s, 150s, 180s, 200s, 250s, 300s. In the present invention, soaking is to drop the solution on the sample and let it stand, so that the interface modification layer can better cover the sample surface, and spin coating is to ensure that the thickness of the interface modification layer is at a relatively thin level to ensure that the charge transfer is not affected.

[0089] In the present invention, when the spin coating method is used for deposition, the spin coating speed can be 2000-4000 r / min, for example, 2000 r / min, 2500 r / min, 3000 r / min, 3500 r / min, 4000 r / min.

[0090] In the present invention, when the spin coating method is used for deposition, the spin coating time can be 10-40 s, for example, 10 s, 15 s, 20 s, 25 s, 30 s, 35 s, or 40 s.

[0091] In the present invention, the liquid phase deposition method may include dissolving the material of the interface modification layer in a solvent to obtain an interface modification layer solution, and then using the interface modification layer solution to deposit the interface modification layer.

[0092] In the present invention, the solvent of the interface modification layer solution may be one or more selected from isopropanol, ethanol and methanol.

[0093] In the present invention, the concentration of the class B modified molecules in the interface modification layer solution can be 0.1-5 mg / mL, preferably 0.1-1 mg / mL, such as 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1.0 mg / mL. In the present invention, the concentration of the class B modified molecules in the interface modification layer solution is controlled within the above preferred range, which is beneficial to improving the hole transport ability of the solar cell and the wettability to the perovskite solution, and then is beneficial to improving the device performance of the perovskite solar cell.

[0094] In the present invention, the concentration of class A modified molecules in the interface modification layer solution can be 0.1-1.0 mg / mL, such as 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1.0 mg / mL. In the present invention, the excessive content of class A modified molecules can reduce the device filling factor due to its poor hole transport capacity, and the too low content has an unobvious effect on the wettability improvement of the perovskite solution on the substrate. The concentration of class A modified molecules within the above range is conducive to improving the hole transport capacity of the solar cell and the wettability of the perovskite solution, and then is conducive to improving the device performance of the perovskite solar cell.

[0095] In the present invention, the deposition of the interface modification layer can be carried out in air or a protective atmosphere, such as a nitrogen atmosphere.

[0096] The method for preparing the interface modification layer of the present invention may further include the steps of performing a first heat treatment, cleaning, and a second heat treatment after the interface modification layer is deposited.

[0097] In the present invention, the temperature of the first heat treatment can be 80-150°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C.

[0098] In the present invention, the time of the first heat treatment can be 5-10 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min.

[0099] In the present invention, the cleaning agent in the cleaning process can be one or more selected from isopropanol, ethanol and methanol.

[0100] In the present invention, the temperature of the second heat treatment can be 80-150°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C.

[0101] In the present invention, the time for the second heat treatment can be 5-10 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min.

[0102] The invention provides a perovskite solar cell comprising the interface modification layer of the invention.

[0103] The present invention provides a perovskite solar cell. The perovskite solar cell may include a transparent conductive substrate, a hole transport layer, an interface modification layer, a perovskite light absorption layer, an electron transport layer and a metal electrode in sequence in the thickness direction. The structure of the perovskite solar cell is as follows: Figure 1 shown.

[0104] In the present invention, the transparent conductive substrate can be a transparent conductive glass substrate, preferably selected from one or more of an indium tin oxide (ITO) transparent conductive glass substrate, a fluorine-doped tin oxide (FTO) transparent conductive glass substrate, an indium zinc oxide (IZO) transparent conductive glass substrate, an aluminum-doped zinc oxide (AZO) transparent conductive glass substrate, an antimony-doped tin oxide (ATO) transparent conductive glass substrate, a cerium-doped indium oxide (ICO) transparent conductive glass substrate and a tungsten-doped indium oxide (IWO) transparent conductive glass substrate.

[0105] In the present invention, the hole transport layer may contain nickel oxide, and the mass fraction of nickel oxide in the hole transport layer may be ≥95%, for example, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5%.

[0106] In the present invention, the nickel oxide in the hole transport layer may have an amorphous structure.

[0107] In the present invention, the hole transport layer may further include a metal oxide other than nickel oxide. Preferably, the metal in the metal oxide may be one or more selected from Li, Cu, Na, Mg, Ca, Sr, Ba and Au. For example, the material of the hole transport layer may be Li 2 O and NiOx compositions (lithium oxide and nickel oxide compositions), CuO and NiOx compositions (copper oxide and nickel oxide compositions), Na 2 O and NiOx composition (sodium oxide and nickel oxide composition), MgO and NiOx composition (magnesium oxide and nickel oxide composition), CaO and NiOx composition (calcium oxide and nickel oxide composition), SrO and NiOx composition (strontium oxide and nickel oxide composition), BaO and NiOx composition (barium oxide and nickel oxide composition), Au 2 O 3 and NiOx compositions (combinations of gold trioxide and nickel oxide).

[0108] In the present invention, the thickness of the hole transport layer may be 15-30 nm, for example, 15 nm, 17 nm, 19 nm, 21 nm, 23 nm, 25 nm, 27 nm, and 29 nm.

[0109] In the present invention, the perovskite light absorbing layer can be ABY 3 The perovskite light-absorbing material of the structure; wherein the A-site ion can be selected from cesium ions (Cs + ), formamidinyl (FA + ) and methylamino (MA + ) in one or more, the B-site ion may be a lead ion (Pb 2+ ) and / or tin ions (Sn 2+), the Y ion may be selected from iodide ions (I - ), bromide ion (Br - ) and chloride ions (Cl - )

[0110] In the present invention, the thickness of the perovskite light absorbing layer may be 400-1000 nm, for example, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm.

[0111] In the present invention, the electron transport layer may include a first electron transport layer and a second electron transport layer in sequence from a thickness direction.

[0112] In the present invention, the first electron transport layer may be C60.

[0113] In the present invention, the second electron transport layer may be 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP).

[0114] In the present invention, the thickness of the first electron transport layer may be 10-40 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, or 40 nm.

[0115] In the present invention, the thickness of the second electron transport layer may be 5-10 nm, for example, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, or 10 nm.

[0116] In the present invention, the thickness of the electron transport layer may be 15-50 nm, for example, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, or 50 nm.

[0117] In the present invention, the perovskite solar cell may be a single-junction perovskite solar cell or a stacked perovskite solar cell.

[0118] In the present invention, the metal electrode may be Cu, Ag or Al.

[0119] In the present invention, the thickness of the metal electrode may be 100-1000 nm, for example, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm.

[0120] The present invention provides a method for preparing the perovskite solar cell of the present invention.

[0121] In the present invention, the method for preparing a perovskite solar cell comprises the following steps:

[0122] (1) depositing a hole transport layer on the surface of a transparent conductive substrate;

[0123] (2) depositing an interface modification layer on the surface of the hole transport layer;

[0124] (3) depositing a perovskite light absorbing layer on the surface of the interface modification layer;

[0125] (4) depositing an electron transport layer on the surface of the perovskite light absorbing layer;

[0126] (5) A metal electrode is deposited on the surface of the electron transport layer to produce a perovskite solar cell.

[0127] In step (1), the method for preparing a perovskite solar cell may further include cleaning the transparent conductive substrate before deposition; preferably, the cleaning process includes cleaning the material of the transparent conductive substrate in water, ultrasonicating in isopropanol, blowing off residual isopropanol with nitrogen, and cleaning with an ultraviolet ozone cleaner. In the present invention, the above cleaning method is used to facilitate the efficient deposition of the hole transport layer.

[0128] In step (1), the hole transport layer material can be deposited on the surface of the transparent conductive substrate by vacuum deposition; preferably, the vacuum deposition method can be magnetron sputtering, electron beam deposition and atomic layer deposition; more preferably, magnetron sputtering.

[0129] In step (1), when magnetron sputtering is used for deposition, the sputtering power can be 90-130W, for example, 90W, 100W, 110W, 120W, 130W.

[0130] In step (1), when magnetron sputtering is used for deposition, the sputtering pressure can be 1-3Pa, for example, 1Pa, 1.5Pa, 2Pa, 2.5Pa, 3Pa.

[0131] In step (1), when magnetron sputtering is used for deposition, the growth temperature can be 150-300°C, for example, 150°C, 200°C, 250°C, 300°C.

[0132] In step (3), the material of the perovskite light absorbing layer is dissolved in a solvent to obtain a perovskite light absorbing layer solution, the perovskite light absorbing layer solution is deposited on the surface of the interface modification layer to obtain a perovskite light absorbing layer precursor, and the perovskite light absorbing layer precursor is annealed to obtain the perovskite light absorbing layer.

[0133] In step (3), the deposition method may be a spin coating method. Preferably, the spin coating method may be a one-step spin coating method or a two-step spin coating method.

[0134] In step (3), when one-step spin coating is used for deposition, the spin coating speed can be 4000-6000 r / min, for example, 4000 r / min, 4500 r / min, 5000 r / min, 5500 r / min, 6000 r / min.

[0135] In step (3), when a one-step spin coating method is used for deposition, the spin coating time can be 20-40 s, for example, 20 s, 25 s, 30 s, 35 s, 40 s.

[0136] In step (3), when the deposition is carried out by a one-step spin coating method, the anti-solvent is added dropwise 5-15 seconds before the spin coating.

[0137] In step (3), when the one-step spin coating method is used for deposition, the anti-solvent can be one or more selected from chlorobenzene (CB), anisole and ethyl acetate.

[0138] In step (3), the solvent of the perovskite light absorbing layer solution may be one or more selected from N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO) and N,N'-dimethylpropylene urea.

[0139] In step (3), the concentration of the material of the perovskite light absorbing layer in the perovskite light absorbing layer solution may be 1-1.5 mol / L, for example, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L.

[0140] In step (3), the annealing temperature can be 80-120°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C.

[0141] In step (3), the annealing time can be 20-30 min, for example, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min.

[0142] In step (4), the electron transport layer can be deposited on the surface of the perovskite light absorbing layer by thermal evaporation or electron beam deposition.

[0143] In step (5), a metal electrode may be deposited on the surface of the electron transport layer by thermal evaporation or electron beam deposition.

[0144] Compared with the prior art, the present invention has the following beneficial effects:

[0145] 1) The wettability of the substrate treated by the present invention is improved, resulting in an increase in the coverage of the perovskite solution on the substrate, thereby improving the coverage of the perovskite light-absorbing layer, providing a basis for large-area preparation;

[0146] 2) The performance of devices prepared by the substrate treated by the present invention is significantly improved in repeatability, which provides a basis for industrial-scale production;

[0147] 3) The interface modification layer of the present invention is universally applicable to the preparation method of nickel oxide. All nickel oxide prepared by vacuum deposition can be treated by the method of the present invention and have similar effects;

[0148] 4) The interface modification layer of the present invention is universal for the types and concentrations of commonly used nickel oxide surface modification materials, has an effect on improving the wettability of devices, and has certain advantages in performance compared to performance comparisons not using the present invention.

[0149] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.

[0150] The ITO transparent conductive glass in Example 1 of the present invention and Comparative Example 1 was purchased from Shangyang Technology.

[0151] Example 1

[0152] This example was prepared according to the following steps Figure 1 Perovskite solar cell shown:

[0153] 1. The ITO transparent conductive glass substrate was cleaned with deionized water, and then ultrasonicated in isopropanol for 30 minutes. The residual isopropanol was blown dry with nitrogen gas from the ultrasonicated ITO transparent conductive glass substrate, and then treated in an ultraviolet ozone cleaning machine for 15 minutes to obtain a transparent conductive substrate;

[0154] 2. Using radio frequency magnetron sputtering technology, lithium-doped nickel oxide (Li 2 O and NiO (mass ratio of 1.04:98.96) are used as a target material, and the target material is deposited on the surface of a transparent conductive substrate to prepare a hole transport layer, wherein the sputtering power is 100 W, the sputtering pressure is 2.5 Pa, the growth temperature is 200 ° C, and the thickness of the hole transport layer is 25 nm;

[0155] 3. Me-4PACz, MeO-2PACz and 4-F-PEACl were dissolved in isopropanol to obtain an interface modification layer solution. In the interface modification layer solution, the total concentration of Me-4PACz and MeO-2PACz was 0.3 mg / mL, the molar ratio of Me-4PACz to MeO-2PACz was 1:1, and the concentration of 4-F-PEACl was 0.5 mg / mL. In a nitrogen atmosphere, the interface modification layer solution was spin-coated on the surface of the hole transport layer by spin coating, wherein the immersion time was 30 s, the spin coating speed was 3000 r / min, and the spin coating time was 20 s. After the spin coating deposition was completed, it was heat treated at 100°C for 10 min to allow the modification layer molecules to react with the nickel oxide surface. After washing with 200 μL of isopropanol, it was heat treated again at 100°C for 10 min to obtain an interface modification layer. The thickness of the interface modification layer was 3 nm.

[0156] 4. Weigh CsI, FAI, MAI, and PbI in a nitrogen glove box 2 and PbBr 2 The preparation component is Cs 0.05 (FA 0.77 MA 0.23 ) 0.95 Pb(I 0.77 Br 0.23 ) 3 The raw material of the perovskite structure material is dissolved in a mixed solvent with a volume ratio of DMF and DMSO of 3:1 to obtain a perovskite light absorbing layer solution with a theoretically generated perovskite structure material concentration of 1.5 mol / L, and the perovskite light absorbing layer solution is deposited on the surface of the interface modification layer by a one-step spin coating method in a glove box to obtain a perovskite light absorbing layer precursor, wherein the one-step spin coating method specifically comprises spin coating the perovskite light absorbing layer solution at 5000 r / min for 30 seconds, and dropping 200 μL of CB as an anti-solvent at the last 10 seconds, and annealing on a hot plate at 100° C. for 25 minutes after the spin coating method deposition is completed to obtain a perovskite light absorbing layer, and the thickness of the perovskite light absorbing layer is 600 nm;

[0157] 5. Using a thermal evaporation device, a 30 nm thick C60 and a 10 nm thick BCP are sequentially deposited on the surface of the perovskite light absorption layer to prepare an electron transport layer;

[0158] 6. Cu with a thickness of 200 nm is deposited on the surface of the electron transport layer by thermal evaporation equipment to obtain a metal electrode and a perovskite solar cell.

[0159] Example 2

[0160] The other conditions of this example are the same as those of Example 1, except that 4-F-PEACl in step 3 of this example is replaced by

[0161] Example 3

[0162] The other conditions of this example are the same as those of Example 1, except that 4-F-PEACl in step 3 of this example is replaced by

[0163] Example 4

[0164] The other conditions of this example are the same as those of Example 1, except that 4-F-PEACl in step 3 of this example is replaced by

[0165] Example 5

[0166] The other conditions of this example are the same as those of Example 1, except that 4-F-PEACl in step 3 of this example is replaced by

[0167] Example 6

[0168] The other conditions of this example are the same as those of Example 1, except that 4-F-PEACl in step 3 of this example is replaced by

[0169] Example 7

[0170] The other conditions of this example are the same as those of Example 1, except that 4-F-PEACl in step 3 of this example is replaced by

[0171] Example 8

[0172] The other conditions of this example are the same as those of Example 1, except that 4-F-PEACl in step 3 of this example is replaced by

[0173] Comparative Example 1

[0174] This comparative example prepares a perovskite solar cell according to the following steps:

[0175] 1. The ITO transparent conductive glass substrate was cleaned with deionized water, and then placed in isopropanol for ultrasonic treatment for 30 minutes. The residual isopropanol was blown dry with nitrogen from the ultrasonicated ITO substrate, and then placed in a UV ozone cleaning machine for 15 minutes to obtain a transparent conductive substrate.

[0176] 2. Using radio frequency magnetron sputtering technology, lithium-doped nickel oxide (Li 2O and NiO (mass ratio of 1.04:98.96) are used as a target material, and the target material is deposited on the surface of a transparent conductive substrate to prepare a hole transport layer, wherein the sputtering power is 100 W, the sputtering pressure is 2.5 Pa, the growth temperature is 200 ° C, and the thickness of the hole transport layer is 25 nm;

[0177] 3. Dissolve Me-4PACz and MeO-2PACz in isopropanol at a molar ratio of 1:1 to obtain an interface modification layer solution. In the interface modification layer solution, the total concentration of Me-4PACz and MeO-2PACz is 0.3 mg / mL, and the molar ratio of Me-4PACz and MeO-2PACz is 1:1. In a nitrogen atmosphere, the interface modification layer solution is spin-coated on the surface of the hole transport layer by spin coating, wherein the immersion time is 30 s, the spin coating speed is 3000 r / min, and the spin coating time is 20 s. After the spin coating deposition is completed, heat treatment is performed at 100°C for 10 min to facilitate the combination reaction between the modification layer molecules and the nickel oxide surface. After washing with 200 μL of isopropanol, heat treatment is performed again at 100°C for 10 min to obtain an interface modification layer. The thickness of the interface modification layer is 3 nm.

[0178] 4. Weigh CsI, FAI, MAI, and PbI in a nitrogen glove box 2 and PbBr 2 The preparation component is Cs 0.05 (FA 0.77 MA 0.23 ) 0.95 Pb(I 0.77 Br 0.23 ) 3 The raw material of the perovskite structure material is dissolved in a mixed solvent with a volume ratio of DMF and DMSO of 3:1 to obtain a perovskite light absorbing layer solution with a theoretically generated perovskite structure material concentration of 1.5 mol / L, and the perovskite light absorbing layer solution is deposited on the surface of the interface modification layer by a one-step spin coating method in a glove box to obtain a perovskite light absorbing layer precursor, wherein the one-step spin coating method specifically comprises spin coating the perovskite light absorbing layer solution at 5000 r / min for 30 seconds, and dropping 200 μL of CB as an anti-solvent at the last 10 seconds, and annealing on a hot plate at 100° C. for 25 minutes after the spin coating method deposition is completed to obtain a perovskite light absorbing layer, and the thickness of the perovskite light absorbing layer is 600 nm;

[0179] 5. Using a thermal evaporation device, a 30 nm thick C60 and a 10 nm thick BCP are sequentially deposited on the surface of the perovskite light absorption layer to prepare an electron transport layer;

[0180] 6. Cu with a thickness of 200 nm is deposited on the surface of the electron transport layer by thermal evaporation equipment to obtain a metal electrode and a perovskite solar cell.

[0181] Test Case

[0182] Perovskite solar cell device performance test: under AM 1.5G standard, optical power density 100mW / cm 2 The JV curve was obtained by testing the current density corresponding to the device at different applied voltages under the device, and the device performance (open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency) of the perovskite solar cells prepared in Examples 1-8 and Comparative Example 1 were obtained according to the characteristic curves. The test results are shown in Table 1.

[0183] (1) Open circuit voltage (V oc ): When the current in the external circuit is 0, the device is in an open circuit state, and the external voltage applied by the external circuit is the open circuit voltage.

[0184] (2) Short-circuit current density (J sc ): When the external voltage is 0, the device is in a short-circuit state, and the current density received by the external circuit is the short-circuit current density.

[0185] (3) Fill factor (FF): The maximum power point per unit area in the JV curve (P max ) to the product of short-circuit current density and open-circuit voltage, that is:

[0186]

[0187] (4) Photovoltaic conversion efficiency (PCE): The efficiency of converting incident solar energy into electrical energy, which is the ratio of the maximum power point per unit area to the incident light power density (P in ), that is:

[0188]

[0189] Table 1: Open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of perovskite solar cells prepared in Examples 1-8 and Comparative Example 1

[0190] <![CDATA[V OC (V)]]> <![CDATA[J SC (mA / cm 2 )]]> FF(%) PCE(%) Example 1 1.24211 20.9962 83.353 21.73814 Example 2 1.23829 21.23169 83.03197 21.82999 Example 3 1.23511 20.91633 82.93314 21.42487 Example 4 1.2311 21.44059 82.60386 21.80371 Example 5 1.23632 21.26594 82.42115 21.66975 Example 6 1.23415 20.93578 82.66548 21.35897 Example 7 1.24766 21.11618 83.47884 21.99313 Example 8 1.24305 21.14802 83.15091 21.85872 Comparative Example 1 1.24023 20.94482 79.99957 20.781

[0191] As can be seen from Table 1, the filling factor and photoelectric conversion efficiency of the perovskite solar cells containing the interface modification compounds of the present invention in Examples 1-8 are significantly higher than the filling factor and photoelectric conversion efficiency of the perovskite solar cell not containing the interface modification compounds of the present invention in Comparative Example 1, and the open circuit voltage and short circuit current density of the two are basically the same, which indicates that the interface modification layer composed of the interface modification compounds of the present invention can effectively improve the device performance of the perovskite solar cell.

[0192] Figure 2This is an optical comparison photograph of the perovskite light absorption layer of the perovskite solar cell prepared in Comparative Example 1 without adding 4-F-PEACl to the interface modification layer and the perovskite light absorption layer of the perovskite solar cell prepared in Example 1 with adding 4-F-PEACl to the interface modification layer (b). Figure 3 Optical comparison photos of the glass surface of the perovskite solar cell prepared without adding 4-F-PEACl to the interface modification layer in Comparative Example 1 (a) and the glass surface of the perovskite solar cell prepared with adding 4-F-PEACl to the interface modification layer in Example 1 (b). Figure 2 and Figure 3 It can be seen that compared with the perovskite light-absorbing layer prepared without adding 4-F-PEACl, the overall coverage of the perovskite light-absorbing layer prepared with the addition of 4-F-PEACl is significantly improved, and the full-area perovskite light-absorbing layer coverage is basically achieved, which is beneficial to the improvement of the performance of perovskite solar cell devices.

Claims

1. An interface modification compound, characterized in that The interface modification compound is a compound of formula I or a compound of formula II: In Formula I, R1-R5 are each independently selected from H, F, C1-C10 alkyl which is unsubstituted or substituted by one or more fluorine groups, and at least one of R1-R5 is F or C1-C10 alkyl which is substituted by one or more fluorine groups; R6 is a single bond, unsubstituted or substituted C1-C10 alkylene; X is a hydrophilic group; In Formula II, R7-R 16 are independently selected from H, F, C1-C10 alkyl which is unsubstituted or substituted by one or more fluorine groups, and R7-R 16 At least one of them is F or a C1-C10 alkyl group substituted by one or more fluorine groups; R 17 and R 18 Each is independently a single bond, unsubstituted or substituted C1-C10 alkylene; X' is a hydrophilic group.

2. The interface modification compound according to claim 1, characterized in that The interface modification compound has one or more of the following characteristics: In Formula I, R1-R5 are each independently selected from H, F and -CF3, and at least one of R1-R5 is F or -CF3; In formula I, R6 is C1-C6 alkylene; In formula I, X is -NH2, -NH3 + Y - , -NR2 or -N + R3Y - , wherein R is a C1-C10 alkyl group and Y is a halogen; In Formula II, R7-R 16 are independently selected from H, F and -CF3, and R7-R 16 At least one of them is F or -CF3; In Formula II, R 17 and R 18 Each is independently C1-C6 alkylene; In formula II, X' is -NH-, -NH2 + Y - -, -NR-, or -N + R - -, wherein R is a C1-C10 alkyl group and Y is a halogen group.

3. The interface modification compound according to claim 1, characterized in that In Formula II, R7-R 11 At least one of them is F or -CF3 and R 12 -R 16 At least one of them is F or -CF3.

4. The interface modification compound according to claim 1, characterized in that The interface modification compound is selected from the following compounds:

5. The interface modification compound according to claim 1, characterized in that The interface modification compound is 4-fluorophenethylammonium chloride or 4-fluorophenethylammonium iodide.

6. An interface modification layer, characterized in that: The interface modification layer comprises class A modification molecules and class B modification molecules, wherein the class A modification molecules are one or more interface modification compounds described in any one of claims 1 to 4, and the class B modification molecules are selected from one or more of self-assembly molecules containing carbazole groups and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine].

7. The interface modification layer according to claim 6, characterized in that: The interface modification layer has one or more of the following characteristics: The self-assembling molecules containing carbazole groups are [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid and / or [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid; In the interface modification layer, the mass ratio of the type B modification molecules to the type A modification molecules is 1:(0.1-50); The thickness of the interface modification layer is 2-5 nm.

8. A method for preparing an interface modification layer, characterized in that: The method comprises the following steps: depositing the interface modification layer according to claim 6 or 7 by liquid phase deposition or vapor phase deposition.

9. The method according to claim 8, characterized in that The interface modification layer is deposited by a liquid phase deposition method, which includes: dissolving a raw material of the interface modification layer in a solvent to obtain an interface modification layer solution, and then using the interface modification layer solution to deposit the interface modification layer.

10. The method according to claim 9, characterized in that The method has one or more of the following features: The deposition of the interface modification layer is carried out in air or a protective atmosphere; The liquid phase deposition method is an immersion method or a spin coating method; The solvent of the interface modification layer solution is selected from one or more of isopropanol, ethanol and methanol; The concentration of the type B modification molecules in the interface modification layer solution is 0.1-5 mg / mL; The concentration of the type A modification molecules in the interface modification layer solution is 0.1-1.0 mg / mL.

11. A perovskite solar cell, characterized in that: The perovskite solar cell comprises the interface modification layer according to claim 6 or 7.

12. The perovskite solar cell according to claim 11, characterized in that The perovskite solar cell comprises, in order from the thickness direction, a transparent conductive substrate, a hole transport layer, an interface modification layer, a perovskite light absorption layer, an electron transport layer and a metal electrode.

13. The perovskite solar cell according to claim 12, characterized in that: The hole transport layer includes nickel oxide.

Citation Information

Cited By

  • Perovskite cell and preparation method therefor, photovoltaic module, power generation device and electric device

    WO2026157847A1